2020
DOI: 10.3352/jeehp.2020.17.23
|View full text |Cite
|
Sign up to set email alerts
|

Nurse educators’ experiences with student incivility: a meta-synthesis of qualitative studies

Abstract: Purpose: This study aimed to synthesize the best available qualitative research evidence on experiences of nurse educators with student incivility in undergraduate nursing classrooms. Methods: A meta-synthesis of qualitative evidence using thematic synthesis was conducted. A systematic search was performed of 12 databases for relevant literature with a publication date limit of March 31, 2019. Two reviewers independently conducted critical quality appraisals using the checklist for qualitative research develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…As suggested by a previous study (Clark & Ritter, 2018), faculty and student representatives should be involved in developing the rules or policies, which should then be reviewed by the appropriate university support departments (including legal). A systematic review study further suggested that essential principles for addressing incivility included maintaining professional behavior between the educator and the students (Park & Kang, 2020). In addition, Park and Kang mentioned that a healthy relationship between educators and students is maintaining professional boundaries and demonstrating mutual respect.…”
Section: Nursing Practicesmentioning
confidence: 99%
See 3 more Smart Citations
“…As suggested by a previous study (Clark & Ritter, 2018), faculty and student representatives should be involved in developing the rules or policies, which should then be reviewed by the appropriate university support departments (including legal). A systematic review study further suggested that essential principles for addressing incivility included maintaining professional behavior between the educator and the students (Park & Kang, 2020). In addition, Park and Kang mentioned that a healthy relationship between educators and students is maintaining professional boundaries and demonstrating mutual respect.…”
Section: Nursing Practicesmentioning
confidence: 99%
“…Moreover, based on a meta-analysis of 11 qualitative studies, Park and Kang discovered that common forms of incivility include side conversations during class, tardiness or early departure, and disagreements during test reviews (Park & Kang, 2020). In addition, more severe incivility, including verbal or nonverbal threats and aggression, were reported (Park & Kang, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Students’ experiences of faculty bullying are globally documented (Prato & Del Prato, 2013; Seibel et al, 2018). The mantra that students are rights‐armed, all‐powerful consumers of the higher education ‘product’, has now emboldened contra power harassment (Christensen et al, 2020; Lampman et al, 2009) where bullying and intimidation of faculty and mentors by students is growing (Park & Kang, 2020). Faculty bullying is so ‘systemic and pervasive’ (Edmonson & Zelonka, 2019, p. 274) as to be barely remarkable (Thompson & Darbyshire, 2013).…”
Section: Nursing Education's Crucible Of Incivilitymentioning
confidence: 99%